2009
DOI: 10.1128/jcm.01939-09
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Multidrug Resistance of Enteric Bacteria following an Intervention To Reduce Antimicrobial Resistance in Dairy Calves

Abstract: An intervention study was conducted to determine whether discontinuing the feeding of milk replacer medicated with oxytetracycline and neomycin to preweaned calves reduced antimicrobial resistance in Salmonella, Campylobacter, and Escherichia coli bacteria. Results demonstrated that the intervention did reduce multidrug resistance in these bacteria but that other factors also influenced multidrug resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…influenced by co-selection due to linkage of resistance genes. But widespread resistance is fundamentally a consequence of historical and current use of antimicrobials and associations between use of antimicrobials and resistance in enteric E. coli of calves have been documented [19,20,22,[25][26][27][28]. However, in the present study resistance is not a direct sequel to antimicrobial use since no calf was treated prior to sampling.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…influenced by co-selection due to linkage of resistance genes. But widespread resistance is fundamentally a consequence of historical and current use of antimicrobials and associations between use of antimicrobials and resistance in enteric E. coli of calves have been documented [19,20,22,[25][26][27][28]. However, in the present study resistance is not a direct sequel to antimicrobial use since no calf was treated prior to sampling.…”
Section: Discussionmentioning
confidence: 55%
“…Although the total use of antimicrobials in the herds is unknown, the absence of association indicates that the high prevalence of resistance is not solely an effect of a direct selection pressure by use of antimicrobials to the calves. Importance of other aspects than antimicrobial use on prevalence of resistant E. coli in preweaned calves is indicated by several studies [17,[20][21][22]26,28,30] and was recently reviewed by Call et al [24]. One proposed factor is a linkage between resistance genes and genes conferring selective advantage to colonize the intestinal lumen of calves.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Svensson et al (2003) suggested that this could be occurring because calves in group pens better meet their social and emotional needs and drink their milk in a more natural way (Svensson et al, 2003). This may be relevant to the selection of resistance in IP calves, because diarrhea in calves has previously been associated with identification of antimicrobial drug resistance (Orden et al, 2000; Kaneene et al, 2009). A study by de Verdier et al (2012) evaluated the relationship between occurrence of diarrhea and prevalence of antimicrobial resistance in fecal E. coli .…”
Section: Discussionmentioning
confidence: 99%
“…The U.S. FDA’s Veterinary Laboratory Investigation and Response Network (Vet-LIRN) is a network of veterinary diagnostic laboratories that investigates potential animal food or drug related issues 19 . In August 2020, an Inter-Laboratory Comparison Exercise Round 1 (ILC1) was collaboratively conducted by FDA and other organizations to qualitatively and quantitatively evaluate the SARS-CoV-2 real-time RT-PCR detection methods used by veterinary diagnostic laboratories 20 .…”
mentioning
confidence: 99%